Depositional Environmental Evolution of Nyalindung Formation based on Paleontology Molluscan Study, Ciodeng Area, Sukabumi, West Java, Indonesia - Aswan Aswan; Elina Sufiati (Indonesian Institute of Sciences, 2021)
This research was conducted to understand and identify changes in the depositional environment of the Nyalindung Formation in the Ciodeng area, Sukabumi, based on mollusk paleontology and lithological associations. Paleontological study of mollusks to interpret the depositional environment becomes important due to the scarcity or absence of foraminifera in mollusk bearing rocks. Foraminifera is commonly used to determine depositional environment. The results of this mollusk paleontology study and lithological associations show at least sixteen changes in depositional environment. The environmental changes range from rivers, mangroves, beaches, tidal areas, shallow marine nearby the coast, shallow open marine, and relatively deeper marine. The depositional environmental changes shown by thissection might be related to tectonic activity and global sea level fall that occurred since the early Late Mioceneto Pleistocene. The sedimentary units in this section are also characterized by predominant fluvial, mangroves, beach, and tidal in the upper layers.